Phonetic Interference of Javanese Language to Sundanese Language: A Case Study - Gustiningsih, Wanda Setiani (2016)
This research aims to investigate the common characteristics of Sundanese pronunciation deviations made by Javanese learners of Sundanese and observe pitch range production by speakers when reading Sundanese text. The participants are six Sundanese speakers and six Javanese learners of Sundanese who came from Central Java and have stayed in Bandung for more than twenty years. The data are collected through a reading task assessment. Beside pitch range analysis, Praat software is also used to analyse a further acoustic phonetic analysis of vowel duration. Results show that the type of pronunciation deviation of non-native speakers is allophonic shift that occurs between /e/ into /ǝ/, /ǝ/ into /e/, and /ɨ/ into /ǝ/ in continuous speech. The vowel duration of Javanese learners of Sundanese is longer compared to the duration of Sundanese speakers. Moreover, the Javanese learners of Sundanese had the higher number of pitch range production compared to the Sundanese speakers. Keywords: Language interference, acoustic phonetic, pitch range, Sundanese speakers and Javanese learners of Sundanese. Penelitian ini bertujuan untuk meneliti karakteristik umum deviasi pengucapan Bahasa Sunda yang dilakukan oleh orang Jawa yang mempelajari Bahasa Sunda dan mengamati produksi jarak nada penutur ketika membaca teks Bahasa Sunda. Partisipan dalam penelitian ini adalah enam penutur Bahasa Sunda and enam orang Jawa yang mempelajari Bahasa Sunda yang berasal dari Jawa Tengah dan telah menetap di Bandung selama lebih dari dua puluh tahun. Data diperoleh melalui sebuah penilaian tes membaca. Selain meneliti jarak nada, perangkat lunak Praat juga digunakan untuk meneliti analisa fonetik akustik lebih lanjut yaitu durasi vokal. Hasil menunjukan bahwa jenis deviasi pengucapan dari orang Jawa yang mempelajari Bahasa Sunda adalah perubahan alofinik antara /e/ menjadi /ǝ/, /ǝ/ menjadi /e/, dan /ɨ/ menjadi /ǝ/ dalam pengucapan terus-menerus. Durasi vokal dari orang Jawa yang mempelajari Bahasa Sunda lebih lama dibandingkan durasi vokal dari penutur Bahasa Sunda. Lebih lanjut, orang Jawa yang mempelajari Bahasa Sunda lebih tinggi dalam produksi jarak nada dibandingkan dengan penutur Bahasa Sunda. Kata Kunci: Interfensi bahasa, akustik fonetik, jarak nada, penutur Bahasa Sunda dan orang Jawa yang mempelajari Bahasa Sunda.